Identifying and prioritizing the opportunities and threats of blockchain technology in the judiciary - Mohsen Shafiei Nikabadi; Mohammad Ali Sangbor; mahdieh sabzalizadeh (حقوق فناوریهای نوین)
Blockchain technology has brought about significant changes in the legal field over the recent years. Decentralized justice platforms have attracted a lot of attention thanks to their goal of increasing individuals’ access to legal services and providing widespread access to justice. However, using decentralized dispute resolution systems instead of traditional centralized systems necessitates a thorough examination of the opportunities and threats of this technology, given the high importance of the judiciary. This study aims to identify and rank the potential advantages and drawbacks of implementing blockchain technology within the judiciary. The study sample comprises a targeted group of information technology professionals from the judiciary. First, the benefits and challenges associated with using blockchain technology were examined comprehensively through a review of current literature. Then, significant indicators were identified using the fuzzy Delphi and ranked through the interpretive structural modeling. Results revealed that the security and accuracy of data processing, limitations on the number of transactions within a blockchain network, network security, interactivity of blockchain networks, disruption of communication due to cyber-attacks, high storage requirements, maintenance and support, data accessibility, and lack of public trust pose serious obstacles to implementing blockchain technology within the judiciary.